nhân 4 lên ta có:
\(4x^2+4y^2+4z^2-4xy-3.4y-2.4y+16=0\)
\(\Leftrightarrow4x^2-4xy+y^2+3.y^2-3.y.4+3.4+4z^2-4.z.2+4.1=0\)
\(\Leftrightarrow\left(2x-y\right)^2+3.\left(y-2\right)^2+4.\left(z-1\right)^2=0\)
từ đây suy ra: \(\hept{\begin{cases}2x=y\\y=2\\z=1\end{cases}}\Rightarrow\hept{\begin{cases}x=1\\y=2\\z=1\end{cases}}\left(tm\right)\)
vậy nghiệm của phương trình là..............
nhân 4 lên ta có:
4x2+4y2+4z2−4xy−3.4y−2.4y+16=0
⇔4x2−4xy+y2+3.y2−3.y.4+3.4+4z2−4.z.2+4.1=0
⇔(2x−y)2+3.(y−2)2+4.(z−1)2=0
từ đây suy ra: {
2x=y |
y=2 |
z=1 |
⇒{
x=1 |
y=2 |
z=1 |